Candid science V : conversations with famous scientists - Hargittai, Balazs (Imperial College Press ; Distributed by World Scientific Pub. Co., 2005)
Candid Science V: Conversations with Famous Scientists contains 36interviews with well-known scientists, including 19 Nobel laureates, Wolf Prize winners, and other luminaries. These in-depth conversationsprovide a glimpse into the greatest achievements in science during thepast few decades, featuring stories of the discoveries, and showingthe human drama behind them.